2011
DOI: 10.1097/brs.0b013e3181d7a81a
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Imaging Prediction of Pseudarthrosis After Anterior Cervical Discectomy and Fusion

Abstract: A threshold level of 4° of motion is commonly used to identify a pseudarthrosis. Our prospective study suggests that this value has a high PPV, but a low specificity and would miss many of the pseudarthroses that have angular motion less than 4° (sensitivity 23%). By lowering the threshold for angular motion to 1°, the sensitivity improves to 77%. CT scan has been touted as the gold standard, and it has a high positive predictive value of 100%. However, its NPV was slightly lower than using 1° of motion on QMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 25 publications
(24 reference statements)
1
31
0
6
Order By: Relevance
“…The Cobb angle measurement is closely associated with the instantaneous center of rotation while obtaining the dynamic cervical spine films, making an accurate and consistent angle measurement difficult. Although there is evidence that combining quantitative motion analysis software with dynamic radiographs may yield objective and reliable numbers compared to manual or subjective measurements, the limitation of specialized technology and software availability make this less useful [ 42 , 47 ]. The difficulty of consistently reproducing the Cobb angle measurement makes this a less appealing method to diagnose pseudoarthrosis for the authors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cobb angle measurement is closely associated with the instantaneous center of rotation while obtaining the dynamic cervical spine films, making an accurate and consistent angle measurement difficult. Although there is evidence that combining quantitative motion analysis software with dynamic radiographs may yield objective and reliable numbers compared to manual or subjective measurements, the limitation of specialized technology and software availability make this less useful [ 42 , 47 ]. The difficulty of consistently reproducing the Cobb angle measurement makes this a less appealing method to diagnose pseudoarthrosis for the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al defined bony fusion as “fused with remodeling and trabeculae present” or “graft intact, not fully remodeled and incorporated, but no lucency present,” which is more of a general vague description of fusion status [ 48 ]. Other CT scan based parameters used the lack of motion in fused segments and at times no specific parameter was described for fusion assessment [ 14 , 28 , 29 , 37 , 47 , 55 ]. Song et al [ 18 ] first described the ExGBB and InGBB on CT scans to subcategorize the areas of achieved fusion in 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that CT provides a higher sensitivity and positive predictive value in diagnosing the presence of successful fusion compared to using X-ray. [7] There are concerns about extraneous radiation from CT over X-ray, however, we still feel that CT should be a preferential modality for assessing arthrodesis status as demonstrated by this case.…”
Section: Discussionmentioning
confidence: 94%
“…Discrepancies among imaging methods may further complicate the comparison of fusion rates among studies, and the results should be interpreted carefully. 11,31 …”
Section: Discussionmentioning
confidence: 99%